Pengaruh Realisasi Growth Rasio Pad Terhadap Pertumbuhan Perekonomian Masyarakat Kabupaten Bojonegoro Periode Tahun 2016-2020 - Edy Suhartono; Ike Susanti (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2022)
Sources of Regional Financing or PAD (Regional Original Income) come from local taxes and regional levies. The increase in Regional Original Income (PAD) must be carried out by the Regional Government to finance their own needs, so that the dependence of the Regional Government on the Central Government is decreasing and in the end the Regional Government can be independent. This research is descriptive quantitative because we have to know how much the PAD target is so that it can meet the needs of the people of Bojonegoro which is adjusted to the GRDP. The higher the realization of the PAD budget, the higher the economic growth or vice versa because with the equation Y=18.96+4.86X , a= 18.96, it shows an economic growth of 18.96 and the amount of realization is 4.86, from the regression coefficient ( R²) obtained is 0.987, it can be ascertained that the effect of the realization of the PAD Budget on Economic Growth is 98% and the remaining 2% is influenced by other variables. The development of PAD realization in Bojonegoro Regency has increased, it is fluctuating. because the growth performance of PAD allocated for facilities and infrastructure for the public cannot be maintained due to the increase so that it tends to decrease.